Beaches’ Expulsion from Paradise: From a Natural to an Artificial Littoral in Tuscany (Italy) - Enzo Pranzini; Irene Cinelli; Giorgio Anfuso (Coasts, 2024)
This study investigated the shoreline evolution of the Tuscany coast (Italy) from 1878–1883 to 2019. The 205 km sandy coastline, divided into 821 sectors, each one 250 m long, was analyzed to understand how human activities have altered this once-pristine coast. Sub-period analyses highlighted the impacts, both positive and negative, of various shore-protection projects. Initially, regional beaches were undeveloped and accreting, except for a few river deltas where alternating phases of erosion and accretion were observed. Coastal erosion began at deltas’ areas due to the reduction in sediment inputs and, at other areas, enhanced by the development of human settlements and tourism activities. This triggered the construction of protection structures that shifted erosion processes downdrift, a process that induced the downdrift extension of the structures (according to the “domino” effect), determining the transformation of a completely natural and resilient environment into a largely rigid one. Beach nourishment projects, mostly using inland quarries, added about 1 million cubic meters of sediment from the 1980s to 2019. Currently, 57.8% of beaches are larger than in the 1880s, 9.4% did not change and 32.8% are narrower. Overall, the Tuscan coast gained 6.5 km2 of beach surface with an average shoreline advancement of 32 m. Recent trends (2005–2019) show that 37.7% of the coast is eroding, 21.1% is stable, and 41.2% is accreting, with a total surface area increase of about 200,000 m2. The beach surface area is still increasing despite the existing reduced sediment input due to the limited sediment loss resulting from the presence of morphological cells enclosed by very prominent headlands and the absence of submarine canyons that would otherwise direct sediments to the continental shelf.